Representação da cultura nordestina na cobertura jornalística da tv anhanguera - to: numa perspectiva folkcomunicacional - Silva, Thiago Douglas (Universidade Federal do Tocantins, 2022)
This research analyzes the representativeness of northeastern culture in Palmas' journalistic coverage, with the aim of identifying the reformulations of northeastern culture in Palmas and its contribution to the construction of palmense identity, the last planned capital of the 20th century. Based on the analysis of two articles published on TV Anhanguera Tocantins, referring to the day of the northeast (of the years 2018 and 2019), a comparative analysis was made between the two reports to identify how the media appropriates this cultural date. Through the theory of Folkcommunication we can identify the cultural representations coming from the figure of the Northeast that resides in Palmas, and how he has been reelaborating his culture to maintain his identity but at the same time integrates the new culture of Palmas.